The Use of Glue as an Embolic Agent in Trauma - Coffman, Kimberly; Joseph, Arthur; Walker, John A.; Lopera, Jorge E. (Seminars in Interventional Radiology, 2025)
Nonoperative management is becoming more common for hemodynamically stable patients with hemorrhagic traumatic injuries. N-butyl 2-cyanoacrylate (NBCA) glue is a safe and effective embolic agent in cases of solid organ traumatic injury, hemorrhage associated with pelvic fractures, as well as deep and superficial trauma. Although glue can be effectively used off-label in these cases (either alone or in combination with other embolization methods, such as microcoils), operators should first understand the mechanism of action, advantages and disadvantages, common applications, and proper preparation and injection techniques to reduce risk of complications such as nontarget embolization, proximal occlusion preventing distal embolization, and microcatheter occlusion.
Keywords: interventional radiology; glue embolization; trauma; N-butyl 2-cyanoacrylate glue